(3OSJhQ GddZIs - (3CHh YHO Gddg HOjY GdReGf GdMSjf Hf EHQGgje GdfWfRj GdCUHgGfj, Pj GddSGfjf,J (B499 (3g` s
(3ChdgG (B:s
(3hHYO agPG OSJhQ GddZI GdYQHjI GdeSJYedI GdeYJeOI GdeCKhQI GdhGQOI ai cJGH Gddg JYGdi hCNHGQ GdQShd Ydjg GdSdGe heUfaGJ GdGOHGA s
(3BNQgG (B:s
(3hGdJi dGJOgd GdYQHjI SJI hgj H L R a d NhHjJ jLeY ddMQha cdgG ai GdOYGA HjJ LRA Gdgd PG daX jYGVO bdGFdGg jWhY CZK TNU GdMSjf HQMeJc s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B229s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B754s
Keywords: (3GddZIs